Islamic community development: Synergy between Indonesia and Yemen in building civilization through da'wah and Sharia economics - Setiawati, Rini; Firsada, Muhammad; Bahrudin, Moh; Saif, Gehad; Dwianto, Agus (International Journal of Innovative Research and Scientific Studies, 2025)
The connection between Islamic Da’wah, Islamic Finance, and Social Networks related to Economic Innovation in the Islamic Communities of Indonesia and Yemen is significant. The research is primarily motivated by an intent to provide an economic understanding of Islamic principles while remaining within the paradigm of the Islamic framework, maintaining its economic relevance through modernization and development. The mixed-methods analysis explores qualitative and quantitative data to examine how these factors together affect economic growth. From the Islamic perspective, especially from the viewpoint of Islamic teachings in terms of social justice, equity, and community welfare, we found that Islamic Da’wah, Islamic Finance, and Social Networks contribute significantly to economic innovation. These components are the driving force for growth and a major source for earning financial gain, and the values of strength that follow are a source of solidarity and mutual benefit. This study potentially makes the first attempt to fill in the gap by linking economic innovations with ethics, alongside the work of Barro [1] as well as Georgy and Nascimento [2] who focused on economic modeling from an Islamic framework. The results provide essential implications for economic policymakers and religious leaders as future innovative guidelines where Islamic economics can lead the way to sustainable economic and social implications. The study highlights how, while Islamic communities drive both economic and social progression through creativity, fairness, and justice, they are also emphasizing the social dimensions of economic progress.